The Influence of HR Service Quality and Organizational Support on Organizational Commitment Through Job Satisfaction as an Intervening Variable - Nurul Intan Sari; Hernawaty; Husni Muharram Ritonga (Yayasan Multidimensi Kreatif, 2026)
This study examines the extent to which HR service quality and perceived organizational support shape employee commitment, positioning job satisfaction as a mediating mechanism among female employees of PT Permodalan Nasional Madani (PNM) Medan Branch. A quantitative-explanatory survey design was adopted. Fifty female employees working outside the HR department were recruited via purposive sampling, in line with the PLS-SEM minimum sample guideline of ten times the maximum number of paths entering any endogen construct (Hair et al., 2021). A five-point Likert-scale questionnaire served as the data collection instrument, and analysis was conducted through PLS-SEM using SmartPLS 4.0. Key findings indicate that: (1) HR service quality exerts a positive and significant effect on both job satisfaction (β = 0.412; p < 0.05) and organizational commitment (β = 0.287; p < 0.05); (2) organizational support likewise positively influences job satisfaction (β = 0.389; p < 0.05) and organizational commitment (β = 0.341; p < 0.05); (3) job satisfaction is a significant predictor of organizational commitment (β = 0.463; p < 0.05); and (4) job satisfaction serves as a partial mediator between both independent variables and organizational commitment.